2016
DOI: 10.1080/13537121.2016.1140348
|View full text |Cite
|
Sign up to set email alerts
|

‘I have two homelands’: constructing and managing Iranian Jewish and Persian Israeli identities

Abstract: Israel and the Islamic Republic of Iran have had a problematic relationship for the last four decades. Despite their tense relations, Israel is home to thousands of Persians and Iran has the second largest Jewish population in the Middle East. There are social, political and psychological obstacles to dual identification. Using qualitative thematic analysis and Identity Process Theory, this article examines the construction and management of Persian/Iranian and Jewish/Israel identities among these groups. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…The individual is, thus, able to order the social environment and anticipate patterns of action and behavior in interactions with these stimuli. For instance, in work on antisemitism in Iran, it has been found that in circumstances where Iranian Jews are categorized by Iranian Muslims as fellow Iranians (that is, in terms of their national identity) they perceived a greater sense of belonging, acceptance and inclusion than when their Jewish identity is rendered salient (Jaspal, 2016). This can be attributed to the fact that people attenuate differences between stimuli within the same category (referred to as "accentuation") and that they accentuate differences between stimuli in different categories (that is "contrast").…”
Section: Social Identity Processesmentioning
confidence: 99%
“…The individual is, thus, able to order the social environment and anticipate patterns of action and behavior in interactions with these stimuli. For instance, in work on antisemitism in Iran, it has been found that in circumstances where Iranian Jews are categorized by Iranian Muslims as fellow Iranians (that is, in terms of their national identity) they perceived a greater sense of belonging, acceptance and inclusion than when their Jewish identity is rendered salient (Jaspal, 2016). This can be attributed to the fact that people attenuate differences between stimuli within the same category (referred to as "accentuation") and that they accentuate differences between stimuli in different categories (that is "contrast").…”
Section: Social Identity Processesmentioning
confidence: 99%